A Critical Review of Conceptualisation and Measurement of Social Inclusion: Directions for Conceptual Clarity - Anis Ben Brik (17413672) (2025)
We apply a synthesis review to revisit the concept, measurement, and operationalisation of social inclusion and exclusion in the context of comparative social policy, integrating the vast literature on the concepts, with the aim of elucidating a clearer understanding of the concepts for use by scholars and policymakers around the planet. In turn, we outline the conceptual development of the concepts, how they have been operationalised through social policy, and how they have been measured at the national and individual levels. Through our review, we identify limitations in extant conceptualisation and measurement approaches and suggest directions for refining conceptual and measurement frameworks to enhance their utility in social inclusion policy, emphasising the concepts’ multidimensional, multilevel, dynamic, and relational essence and highlighting their connection to related concepts such as social capital, social integration, and social citizenship. Other Information Published in: Social Policy and Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/s1474746425000302